Aging and neuroinflammation: Changes in immune cell responses, axon integrity, and motor function in a viral model of progressive multiple sclerosis. Issue 9 (6th August 2021) - Mestre, Leyre; Alonso, Graciela; Feliú, Ana; Mecha, Miriam; Martín, Carolina; Villar, Luisa M.; Guaza, Carmen
Abstract: Although aggravated multiple sclerosis (MS) disability has been reported in aged patients, the aging impact on immune cells remodeling within the CNS is not well understood. Here, we investigated the influence of aging on immune cells and the neuroinflammatory and neurodegenerative processes that occur in a well‐established viral model of progressive MS. We found an anomalous presence of CD4 + T, CD8 + T, B cells, and cells of myeloid lineage in the CNS of old sham mice whereas a blunted cellular innate and adaptive immune response was observed in Theiler's murine encephalomyelitis virus (TMEV) infected old mice. Microglia and macrophages show opposite CNS viral responses regarding cell counts in the old mice. Furthermore, enhanced expression of Programmed Death‐ligand 1 (PD‐L1) was found in microglia isolated from old TMEV‐infected mice and not in isolated CNS macrophages. Immunocytochemical staining of microglial cells confirms the above differences between young and old mice. Age‐related axonal loss integrity in the mouse spinal cord was found in TMEV mice, but a less marked neurodegenerative process was present in old sham mice compared with young sham mice. TMEV and sham old mice also display alterations in innate and adaptive immunity in the spleen compared to the young mice. Our study supports the need of new or adapted pharmacological strategies for MS elderly patients. Abstract : A review of CNS immune changes of Theiler's virus‐infected mice at young (12 weeks after infection) and old age (40 weeks after infection). The type of changes in the response to viral infection results of the comparison with the corresponding changes observed in young and old sham mice. The age‐associated immune dysfunction may reduce the ability of the immune system to respond efficiently to the pathological consequences induced by Theiler's murine encephalomyelitis virus during the later chronic phases of the disease.